Clinical and Demographic Characteristics of the Patients Operated on for Glaucoma - V. A. Machekhin; O. L. Fabrikantov; V. A. L’vov (Oftalʹmologiâ, 2018)
Purpose: To analyze the results of operation in patients with glaucoma depending on its stage, terms of follow-up and detection.Patients and methods. 102 patients (204 eyes) operated on at IRTC “Eye Microsurgery” Tambov branch within October-November 2017 were examined. Mean age was 69.6 ± 9.5 years old. There were 58 male and 44 female. Patients’ eyes were divided into 4 groups: eyes with absolute glaucoma (33), III stage of glaucoma (71), I–II stage of glaucoma (54) and healthy eyes (46). The age of glaucoma patients in all groups was almost identical: age 60-69 years old (47.7%) and 70–79 (31.3%) prevailed.Results. The mean follow-up period was 2.2 years (from 1 week to 11 years), the average number of examinations per patient in a year was 5. Before the first surgery 16% of the eyes with absolute glaucoma were detected, 40% — with III stage glaucoma, 26.5% — I–II stage glaucoma, the rest 17.5% were healthy (paired) eyes. Within the total follow-up 211 antiglaucomatous and 36 cataract surgeries were performed. The marked visual improvement was not noted after antiglaucomatous surgeries. In 5 patients without any glaucoma symptoms but followed up during 5-10 years without interruption absolute glaucoma was revealed. Among the above mentioned patients 3 had a rather high level of tolerant pressure (17 mm Hg) and high true IOP (25 mm Hg), other 2 — low tolerant pressure (12–14 mm Hg) and normal true IOP (19–20 mm Hg).Conclusion. If glaucoma is diagnosed based on the examinations and patient received treatment, he/she should be under the supervision of an experienced ophthalmologist who determine and change treatment in time, including early surgery.